Rancang Bangun Sistem Informasi Pemantauan Dan Pengendalian Pada Kantor Badan Kepegawaian Negara Regional II - Pratama, Taufik Yudha; Setyawan, Henry Bambang; Arnandy, Didiet Anindita (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Abstract: The administrative file monitoring application serves to determine the extent to which the course of the management of administrative records. The administrative file services include the completion of Decree (SK) retired, cards employee, cards wife (Karis) and cards husband (KARSU), SK promotion, SK relocate the working area, until the determination of candidates for Civil Servants (CPNS), Review Work Period (PMK), Mutation family, dependents leave outside the State (CLTN), the appointment of civil servants over 2 years (C2). Of the existing system there be some problems including the lack of monitoring facilities in each part file, do not report how many files that are already resolved and unresolved and the absence of sorting and search facility on incoming files by date and name of the local agencies. Of the existing problems will require monitoring and file control information system for the BKN Regional II, so it can help the BKN Regional II monitor administrative file in and out of each agency areas in the district or city throughout East Java.